160k views
15 votes
-3(x-4) = -9(x - 1)
X=?

1 Answer

2 votes

Answer:

x = - 1/2

Explanation:

-3(x-4) = -9(x - 1)

1. Distributive Property

-3 * x -3 *-4 = -9 * x -9 * -1

-3x + 12 = -9x + 9

Hint: 2 negatives make a postive

-3x + 12 = -9x + 9

2. Subtract 12 on both sides

-3x + 12 - 12 = -9x + 9 - 12

-3x = -9x + -3

3. Add 9x on both sides

-3x + 9x = -9x + 9x + -3

6x = -3

4. Divide both sides by 6 to isolate the variable

6x/6 = -3/6

x = - 1/2

Check:

-3(-1/2-4) = -9( -1/2- 1)

3/2 + 12 = 9/2 + 9

3/2 + 12 ( we need a common denominator so...lets make it 2 )

3/2 + 12*2/1*2

3/2 + 24/2 = 27/2 = 13 1/2 = 13. 5

Now...

9/2 + 9 ( we need a common denominator so..lets make it 2 )

9/2 + 9*2/1*2

9/2 + 18/2 = 27/2 = 13 1/2 = 13.5

13.5 = 13.5 CORRECT!

27/2 = improper fraction

13 1/2 = mixed number

13.5= decimal form

Hope this helped

User Greg Wang
by
5.3k points